Lymphadenectomy during pulmonary metastasectomy: Impact on survival and recurrence. Issue 4 (11th July 2019) - Londero, Francesco; Morelli, Angelo; Parise, Orlando; Grossi, William; Crestale, Sara; Tetta, Cecilia; Johnson, Daniel M.; Livi, Ugolino; Maessen, Jos G.; Gelsomino, Sandro
Abstract: Background and Objectives: Lymphadenectomy during pulmonary metastasectomy (PM) is widely carried out. We assessed the potential benefit on patient survival and tumor recurrence of this practice. Methods: One hundred eighty‐one patients undergoing a first PM were studied. Eighty‐six patients (47.5%) underwent lymphadenectomy (L+ group) whereas 95 (52.5%) did not undergo nodal harvesting (L−group). Main outcomes were overall survival (OS) and disease‐free survival (DFS). Median follow‐up was 25 months (interquartile range [IQR], 13‐49). Results: At follow‐up 84 patients (46.4%) died, whereas 97 (53.6%) were still alive with recurrence in 78 patients (43%). There was no difference in 5‐year survival (L+ 30.0% vs L− 43.2%; P  = .87) or in the 5‐year cumulative incidence of recurrence (L + 63.2% vs L−80%; P  = .07) between the two groups. Multivariable analysis indicated that disease‐free interval (DFI) less than 29 months ( P  < .001) and lung comorbidities ( P  = .003) were significant predictors of death. Metastases from non‐small–cell lung cancer increased the risk of lung comorbidities by a factor of 19.8, whereas the risk of DFI less than 29 months was increased nearly 11‐fold. Competing risk regression identified multiple metastases ( P  = .004), head/neck primary tumor ( P  = .009), and age less than 67 years ( P  = .024) as independent risk factors for recurrence. Conclusion: Associated lymphadenectomy showed not to give any additional advantage in terms of survival and recurrence after PM.